Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Certainly! Let's address each sequence step by step.
### Part (a)
The first sequence provided is:
[tex]\[ \frac{1}{3}, \frac{5}{6}, \frac{9}{9}, \frac{13}{12}, \frac{17}{15}, \ldots \][/tex]
Step 1: Identify the general term
To find the general term \(a_n\), let's observe the pattern in the numerators and denominators separately.
- Numerator pattern: The numerators are \(1, 5, 9, 13, 17, \ldots\)
This appears to be an arithmetic sequence with the first term 1 and a common difference of \(4\):
[tex]\[ a_n = 4n - 3 \][/tex]
- Denominator pattern: The denominators are \(3, 6, 9, 12, 15, \ldots\)
This is an arithmetic sequence with the first term 3 and a common difference of \(3\):
[tex]\[ d_n = 3n \][/tex]
Combining these observations, the general term for the sequence is:
[tex]\[ a_n = \frac{4n - 3}{3n} \][/tex]
Step 2: Calculate the 6th and 7th terms
Using the general term \(a_n\):
- For \(n = 6\):
[tex]\[ a_6 = \frac{4(6) - 3}{3(6)} = \frac{24 - 3}{18} = \frac{21}{18} = \frac{7}{6} \][/tex]
- For \(n = 7\):
[tex]\[ a_7 = \frac{4(7) - 3}{3(7)} = \frac{28 - 3}{21} = \frac{25}{21} \][/tex]
Thus, the next two terms in the sequence are \(\frac{7}{6}\) and \(\frac{25}{21}\).
### Part (b)
The second sequence provided is:
[tex]\[ 2, 7, 12, 17, 23, \ldots \][/tex]
Step 1: Identify the general term
This sequence is strictly increasing by the same difference each time, making it an arithmetic sequence.
- The first term \(b_1 = 2\)
- The common difference \(d = 7 - 2 = 5\)
The general formula for the \(n\)-th term of an arithmetic sequence is:
[tex]\[ b_n = a + (n-1)d \][/tex]
Substituting \(a = 2\) and \(d = 5\), we get:
[tex]\[ b_n = 2 + (n-1)5 = 2 + 5n - 5 = 5n - 3 \][/tex]
Step 2: Calculate the 6th and 7th terms
Using the general term \(b_n\):
- For \(n = 6\):
[tex]\[ b_6 = 5(6) - 3 = 30 - 3 = 27 \][/tex]
- For \(n = 7\):
[tex]\[ b_7 = 5(7) - 3 = 35 - 3 = 32 \][/tex]
Thus, the next two terms in the sequence are \(27\) and \(32\).
### Summary
For the sequences provided:
(a) The general term is:
[tex]\[ a_n = \frac{4n - 3}{3n} \][/tex]
The next two terms after \(\frac{17}{15}\) are:
[tex]\[ \frac{7}{6}, \frac{25}{21} \][/tex]
(b) The general term is:
[tex]\[ b_n = 5n - 3 \][/tex]
The next two terms after \(23\) are:
[tex]\[ 27, 32 \][/tex]
### Part (a)
The first sequence provided is:
[tex]\[ \frac{1}{3}, \frac{5}{6}, \frac{9}{9}, \frac{13}{12}, \frac{17}{15}, \ldots \][/tex]
Step 1: Identify the general term
To find the general term \(a_n\), let's observe the pattern in the numerators and denominators separately.
- Numerator pattern: The numerators are \(1, 5, 9, 13, 17, \ldots\)
This appears to be an arithmetic sequence with the first term 1 and a common difference of \(4\):
[tex]\[ a_n = 4n - 3 \][/tex]
- Denominator pattern: The denominators are \(3, 6, 9, 12, 15, \ldots\)
This is an arithmetic sequence with the first term 3 and a common difference of \(3\):
[tex]\[ d_n = 3n \][/tex]
Combining these observations, the general term for the sequence is:
[tex]\[ a_n = \frac{4n - 3}{3n} \][/tex]
Step 2: Calculate the 6th and 7th terms
Using the general term \(a_n\):
- For \(n = 6\):
[tex]\[ a_6 = \frac{4(6) - 3}{3(6)} = \frac{24 - 3}{18} = \frac{21}{18} = \frac{7}{6} \][/tex]
- For \(n = 7\):
[tex]\[ a_7 = \frac{4(7) - 3}{3(7)} = \frac{28 - 3}{21} = \frac{25}{21} \][/tex]
Thus, the next two terms in the sequence are \(\frac{7}{6}\) and \(\frac{25}{21}\).
### Part (b)
The second sequence provided is:
[tex]\[ 2, 7, 12, 17, 23, \ldots \][/tex]
Step 1: Identify the general term
This sequence is strictly increasing by the same difference each time, making it an arithmetic sequence.
- The first term \(b_1 = 2\)
- The common difference \(d = 7 - 2 = 5\)
The general formula for the \(n\)-th term of an arithmetic sequence is:
[tex]\[ b_n = a + (n-1)d \][/tex]
Substituting \(a = 2\) and \(d = 5\), we get:
[tex]\[ b_n = 2 + (n-1)5 = 2 + 5n - 5 = 5n - 3 \][/tex]
Step 2: Calculate the 6th and 7th terms
Using the general term \(b_n\):
- For \(n = 6\):
[tex]\[ b_6 = 5(6) - 3 = 30 - 3 = 27 \][/tex]
- For \(n = 7\):
[tex]\[ b_7 = 5(7) - 3 = 35 - 3 = 32 \][/tex]
Thus, the next two terms in the sequence are \(27\) and \(32\).
### Summary
For the sequences provided:
(a) The general term is:
[tex]\[ a_n = \frac{4n - 3}{3n} \][/tex]
The next two terms after \(\frac{17}{15}\) are:
[tex]\[ \frac{7}{6}, \frac{25}{21} \][/tex]
(b) The general term is:
[tex]\[ b_n = 5n - 3 \][/tex]
The next two terms after \(23\) are:
[tex]\[ 27, 32 \][/tex]
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.